One year of Lamivudine therapy for portuguese patients with chronic hepatitis B. - Areias, J (2003)
OBJECTIVE: To further verify the efficacy and safety of locally manufactured lamivudine on patients with chronic hepatitis B (CHB). METHODS: 2200 patients with CHB were recruited and received lamivudine orally 100 mg once daily for 12 months. The efficacy assessments included virologic response rate (defined by the absence of serum HBV DNA, HBeAg loss and HBeAg/HBeAb seroconversion), percentage of patients with normalization of alanine aminotransferase (ALT). Meanwhile improvement of quality of life (QOL) measured by mos SF-36 QOL questionnaire and liver histology evaluation were conducted in some patients. The safety assessments included adverse events, serious adverse events and laboratory abnormalities. All 2200 patients received at least one dose of medication and were all included in the safety population. RESULTS: Ninety seven percent of patients (2137/2200) recruited were HBV DNA positive by dot blot (sensitivity GRT or equal to 1.0 pg/ml) at baseline. At the end of 12 months treatment, HBV DNA was undetectable in 80% patients (1538/1920) with HBV DNA positive before treatment. Among the 79%(1744/2200) of the patients recruited had positive HBV DNA accompanied abnormal ALT levels at baseline, 72% patients became ALT normal. And among the 84% (1843/2200) of the patients recruited were HBV DNA and HBeAg positive, anti-HBe negative, 16% (269/1650) patients achieved HBeAg/HBeAb seroconversion after 12 months of lamivudine treatment. The HBeAg/HBeAb seroconversion rate was positive correlation to the ALT level before treatment. A total of 304 patients completed the health-related QOL questionnaire. After 12 months treatment, lamivudine improved both their physical and mental health, especially for their mental health. 133 evaluable, paired liver biopsies were obtained for histological assessment, among whom 115 patients had abnormal ALT levels at baseline. Compared with pre-treatment most of their liver injury got alleviated (51.9%) or no further deterioration (36%), only 12% worsening. During the 12 months treatment, 9% patients withdrew from the study and 17% patients showed at least one adverse event, mild or moderate. There were no obvious difference between this study and the previously reported lamivudine Phase II or III study with regard to the kinds, incidence and severity of adverse events. CONCLUSION: The efficacy and safety profile of the locally manufactured lamivudine 100 mg tablets are similar with those of the previously reported available lamivudine tablets imported in treating Chinese chronic hepatitis B patients.